The Pragmatic Analysis of Politeness Strategies used by the Character of “Turning Red” Movie Script - Zahro, Fatimatuz; Candraloka, Olyvia Revalita (Universitas Negeri Gorontalo, 2025)
Film also brings many things to learn, including politeness. This qualitative descriptive study investigates the politeness strategies employed by the underrated characters in the film Turning Red, with a particular focus on the character Jin. The objective of the research is to analyze how assertive and non-assertive politeness strategies are used by Jin and to explore their implications for English language teaching and learning. To identify which characters to analyze, the researchers conducted a document analysis of fan comments gathered from online platforms such as Moviepedia and Looper, ensuring that audience perceptions guided the selection of underrated figures. After identifying the characters, the researchers used the official movie script and examined it through Brown and Levinson’s (1987) politeness framework, following the steps of data reduction, data display, and conclusion drawing outlined by Miles et al. (2014). The findings reveal that assertive strategies, especially informative acts, were predominant in Jin’s speech, highlighting his role as a calm, supportive problem solver in the film’s family dynamics. Importantly, this study provides meaningful insights for English as a Foreign Language (EFL) learning, showing how analyzing politeness in authentic media can enhance learners’ pragmatic competence, cultural awareness, and communication skills. By linking media analysis with language education, the study underscores the value of films like Turning Red as resources for developing both linguistic and intercultural competence among EFL learners.